One Path Does Not Fit All: A Career Path Approach to the Study of Professional Women Entrepreneurs. (November 2021) - Merluzzi, Jennifer; Burt, Ronald S.
We establish a career path framework to study professional women entrepreneurs. In our framework, we differentiate women by level of engagement (focused, side, never) and career patterns (continuous, interrupted) involving self-employment during their careers. We assert that these career paths will shape identities that will be differentially associated with gendered evaluations of success across women. Leveraging career data on over 800 women graduates from a U.S. business school over 60 years, we present evidence consistent with our thesis, demonstrating the importance of starting from a baseline that allows for women's variances rather than a singular expectation of "lesser" women entrepreneurs.